Effects of high pressure on microbiologically induced calcium carbonate precipitation of methane hydrate-bearing sand layers - Joyce Nakayenga; Toshiro Hata; Alexandra Clarà Saracho; Stuart Kenneth Haigh (Soils and Foundations)
Sporosarcina newyorkensis is an indigenous microbe found in sedimentary layers bearing methane hydrates in the oceans around Japan’s main islands. It can survive extremely cold temperatures and precipitate calcium carbonate (CaCO3). This has led to interest in applying the microbe in microbiologically induced calcium carbonate precipitation (MICP) to improve the properties of the surrounding sand and to facilitate the exploration of methane hydrates. Using the injection method, a large-scale laboratory experiment was conducted in this study on sand columns with a diameter of 60 cm and a height of 70 cm to evaluate the MICP performance of S. newyorkensis under high overburden pressures of 3.5 and 20 MPa. The results indicated that S. newyorkensis can precipitate CaCO3 at high overburden pressures and reduce the permeability of sand. The unconfined compressive strength and amount of precipitated CaCO3 were seen to decrease with the distance from the injection well, but they remained sufficient to distances of up to 20 cm. S. newyorkensis was also found to increase the pH level, which would further promote CaCO3 precipitation and, in turn, lower hydraulic conductivity and stabilize hydrate-bearing sand formations.